Is The "See and Treat" Approach Appropriate for Management of Women with Abnormal Cervical Cytology in Thailand? - Chumnan Kietpeerakool; Jatupol Srisomboon (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
At present, the "see and treat" approach for women with abnormal cervical cytology is widely accepted. It has been proven to be more cost-effectiveness than conventional management, making it particularly attractive for many regions in Thailand where resources are limited and poor patients' compliance is expected. However, the main disadvantage of the "see and treat" approach is the risk of overtreatment. National Health Service (NHS) guidelines recommend that the overtreatment rate in the "see and treat" approach must be less than 10%. The overtreatment rate appears to be acceptable if the "see and treat" approach is carried out in women with high-grade squamous intraepithelial lesion (HSIL) cytology or in women with lesser grades of smear abnormality whose colposcopic findings suggest high-grade disease.